PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PKN KELAS III SDN 106814 TEMBUNG - Yulia Nesti; Samsul Bahri (Jurnal Inovasi Penelitian, 2022)
This research is a research and development (Reseach and Development). Then the product of this development research in the form of video learning media. This study uses the ADDIE (Analysis – Design – Development – implement – Evaluate) model which has been modified into 3D, namely Analysis, Design, and Development. The media developed was validated by one media expert and one material expert. Validation by media experts was carried out in 2 stages and resulted in a product in the form of video media that was appropriate for third grade SDN students. Validation by material experts was carried out in 2 stages and resulted in a product in the form of video media that was appropriate for third grade SDN students. Thus the learning video media developed was declared suitable for use in learning.